Preclinical pharmacokinetic studies and prediction of human PK profiles for Deg-AZM, a clinical-stage new transgelin agonist - Gu, Xiaoting; Li, Xiaohe; Tian, Weixue; Zheng, Chaoyue; Cai, Yutian; Xu, Xiang; Zhao, Conglu; Liu, Hongting; Sun, Yao; Luo, Zhilin; Zhu, Shuwen; zhou, Honggang; et al. (Frontiers in Pharmacology, 2024)
Introduction Deglycosylated azithromycin (Deg-AZM), a newly developed Class I drug with good therapeutic effects on slow transit constipation, is a small-molecule transgelin agonist that has been approved for clinical trials in 2024. The preclinical pharmacokinetic profile of Deg-AZM was investigated to support further development. Methods A LC-MS/MS method was established and validated to detected the concentration of Deg-AZM in various biological samples. In vivo tests such as pharmacokinetic studies in rats and dogs, tissue distribution studies in rats, and extraction studies in rats were conducted to investigated the preclinical pharmacokinetic behaviors of Deg-AZM comprehensively. The plasma protein rate of Deg-AZM was determined by rapid equilibrium dialysis method in vitro. The metabolic stability and metabolite profile of Deg-AZM was assessed using pooled mice, rats, dogs, monkeys and humans microsomes in vitro. The PK profiles of Deg-AZM in human was predicted based on physiologically based pharmacokinetic (PBPK) models. Results The plasma protein binding rates of Deg-AZM were lower in mice and rats, higher in dogs, and moderate in humans. The metabolic process of Deg-AZM was similar in rat and human liver microsomes. From Pharmacokinetic studies in rats and dogs, Deg-AZM was rapidly absorbed into the blood and then quickly eliminated. Plasma exposure of Deg-AZM was dose dependent with no accumulation after continuous gavage administration. In addition, there is no significant gender difference in the pharmacokinetic behavior of Deg-AZM. Deg-AZM was widely distributed in the tissues without obvious accumulation, and mainly excreted from the urinary excretion pathway. Furthermore, the pharmacokinetic profiles of Deg-AZM in humans showed dose dependency. Conclusion The pharmacokinetic profiles of Deg-AZM was fully explored, these results could provide valuable information to support the first-in-human dosage prediction and phase I clinical design.